Googling Politics: How Offloading Affects Voting and Political Knowledge. Issue 1 (29th September 2020) - Kleinberg, Mona S.; Lau, Richard R.
Abstract : Studies suggest that individuals are less likely to process information they can easily look up. Instead of committing information to memory, they rely on the Internet to store information for them—a phenomenon known as "offloading." We examine the effects of offloading on political knowledge and voting behavior. Using data from a 10‐wave panel experiment designed to study information processing in two distinct information environments, we demonstrate that people whose environment is conducive to offloading learn more during an election campaign than individuals whose information environment is not conducive to offloading, even though they look at less information during the campaign. Individuals in the offloading condition also make better vote choices despite examining less information. These results suggest that offloading reduces cognitive load, thereby freeing up processing space in working memory, which can increase learning of information that is accessed, and improve decision‐making.